MENINGKATKAN KEMAMPUAN MENGENAL BINATANG TERNAK PADA ANAK KELOMPOK A MELALUI VIDIO CANVA - Fathul Jannah; Samsul Mujtahidin; Sry Anita Rachman; Farlina Hardianti (JURNAL ASIMILASI PENDIDIKAN, 2024)
This research aims to increase children's achievements in getting to know livestock through Canva videos at Ra Almannan Bagik Nyaka, East Lombok Regency.  Researchers used classroom action research (PTK) with a chemical model with stages, planning, implementation, observation, reflection which are descriptive statistics by explaining each percentage obtained at each session. The subjects in this study were group A with 13 children in Ra Almannan Bagik Nyaka. The research results showed that the percentage in cycle one was 39% and in cycle two it was 77% which was declared successful with a KKM value of 75%.